Pengaruh Etika Periklanan Dalam Komunikasi Pemasaran Terhadap Persepsi Konsumen - Deni Arya Saputra; Ahmad Muthoriqqy Andika Saputra; Refansyah Adi Putra; Daniel Handoko (STIKes Ibnu Sina Ajibarang, 2024)
This article discusses the influence of advertising ethics in marketing communication on consumer perception using a qualitative descriptive approach. The main objective of this study is to explore how ethical practices in advertising affect consumers' perceptions of brands and advertised products. The research methodology involves qualitative analysis of relevant literature and case studies of controversial advertising campaigns. Findings from this research indicate that advertising ethics play a crucial role in shaping consumer perceptions of a brand, influencing consumer loyalty, and long-term brand reputation. The practical implication of this article underscores the necessity of implementing stringent ethical standards in every aspect of marketing communication to foster positive relationships between brands and consumers.